(untitled) (Biological Sciences - PJSIR, 2002)
Hydrazine (HZ) derivative with 2-hydroxyn aphthaldehyde(HN) eluted with methanol: acetonitrile: water (95: 1:4 v/v/v) from reverse phase HPLC column Microsorb C-18, 5µm with UV detection at 330nm. Hydrazine, thiosemicarbazide (TSC) and phenylthiosemicarbazide (PTSC) derivatives of HN also separated when eluted with methanol: Chloroform: acetonitrile: water (65:4 :2:29 V/V/V/V) with a flow rate 1 ml/minute, with detection limit in a ran ge 0.54 to 16 ng/ injection (10µ1). Linear calibration curve for HZ was obtainedwith 0.54-2 .7µg/ml. The effect of variables on the determination of HZ was examined and method has been proposed for the determination of HZ from water.